2008 IEEE Power and Energy Society General Meeting - Conversion and Delivery of Electrical Energy in the 21st Century 2008
DOI: 10.1109/pes.2008.4596022
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and design of the shaded pole single phase asynchronous Motor

Abstract: The Shaded Pole Single Phase Asynchronous Motor represents one of the most common and popular electric machines used for general purpose. It is a peculiar application in electric machinery because even if it is characterized by large scale production volumes and easiness in construction, the Shaded Pole Asynchronous Motor is also known as a complex technological appliance from the point of view of the electric machines theory because of its difficulty to be studied and modelled. The aim of this paper is to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Magnetic stirrers typically use an induction motor called a shaded pole motor. This motor is an alternating current (ac), single phase, asynchronous, squirrel cage rotor, featuring low cost and high durability; however, they have low efficiency and low torque. This motor class is used in various domestic equipment, mostly fans used in microwave ovens, fryers, grills, dryers, freezers, etc .…”
Section: Detecting the Problemmentioning
confidence: 99%
“…Magnetic stirrers typically use an induction motor called a shaded pole motor. This motor is an alternating current (ac), single phase, asynchronous, squirrel cage rotor, featuring low cost and high durability; however, they have low efficiency and low torque. This motor class is used in various domestic equipment, mostly fans used in microwave ovens, fryers, grills, dryers, freezers, etc .…”
Section: Detecting the Problemmentioning
confidence: 99%
“…When studies in the literature are examined, Pessina and Morra found that the component of the magnetic field rotating in the opposite direction of the double short circuit ring motor is less and therefore the vibrations in the torque characteristic are reduced [5]. Makowski obtained the electromagnetic torque value and performance characteristic by considering the saturation and skewing of the rotor bars [6].…”
Section: Introductionmentioning
confidence: 99%